Biowaste orange peel incorporated chitosan/polyvinyl alcohol composite films for food packaging applications - Terzioğlu, Pınar; Güney, Fatma; Parın, Fatma Nur; Şen, İbrahim; Tuna, Sibel (Elsevier Ltd, 2021)
Ecofriendly chitosan/polyvinyl alcohol (PVA) composite films enriched with orange peel were developed by solvent casting technique. The effect of various orange peel contents (0.25–1.25 % w/w) on the barrier, bioactivity, color, microstructure, mechanical, optical, physical, structural, and wettability properties of the chitosan/PVA films were investigated. Fourier Transform Infrared spectroscopy results showed the interaction between the orange peel and the polymers. The addition of orange peel increased the thickness, flexibility, thermal stability and water vapor permeability of the chitosan/PVA films. Orange peel loading improved the ultraviolet–visible light barrier characteristic of neat films by lowering the transparency value. The presence of orange peel in the composite films resulted in decrease of hydrophobicity and oxygen transmission rate. Furthermore, orange peel notably improved the antioxidant activity of films. Consequently, chitosan/polyvinyl alcohol/orange peel composite films may be potential ecofriendly bioactive packaging candidates for food preservation.
Keywords: Bio-based packaging; Orange peel; Polyvinyl alcohol; Chitosan; Composite film